EVALUATION OF PATIENTS’ SATISFACTION IN TELEMEDICINE SERVICE QUALITY: A CASE STUDY ON MAIZBHANDERI FOUNDATION, FATIKCHARI, BANGLADESH - Hoque, Syed Irfanul; Karim, Asif Mahbub; Hossen, Md. Rabiul; Arjumand, Dina (American Economic & Social Review, 2021)
Telemedicine provides healthcare services to the patients through the adaptation of a telecommunication system, as opposed to the face-to-face conventional way of visiting a hospital and doctor’s chamber. In the new-normal situation during COVID 19, telemedicine is a new way forward in the absence of conventional appointments with doctors to ensure regular health services. It is important to evaluate patients’ satisfaction with service qualities and their perception of telemedicine service. The study proposed a conceptual framework based on the e-SERVQUAL model and TAM model to evaluate the service qualities and customers’ satisfaction. Data has been collected through a telephone questionnaire survey from the patients through the psychiatric department who have received healthcare services provided by Maizbhanderi Foundation. Data has been analyzed using IBM SPSS Statistics version 23 according to the patients’ responses on the service qualities including responsiveness, reliability, information quality, empathy, ease of use, perceived usefulness, and their satisfaction with the telemedicine service. The study used Spearman Rank Co-relation to evaluate the co-relation of service qualities with customer satisfaction following the conceptual framework of the study. The result shows a positive co-relation of service qualities with customers’ satisfaction. The study will help to determine the customers’ satisfaction with service qualities using technology.